A Study of the Relationship between Celebrity Endorsement and Customer Experience among Egyptian Youth - El-Arabawy, Sara; Kortam, Wael; Gad, Ghada (Archives of Business Research, 2025)
Celebrity endorsement is extremely used nowadays by companies, as it has become the multimillion industries in the world. Celebrities give the companies an edge to achieve their aims besides increasing the brand viewership. Moving to customer experience, it becomes an essential point in managerial texts and academic agenda that after globalization, customers become more educated and don’t accept less than superior value. Based on the above idea that both celebrity endorsement and customer experience are the major hot topics nowadays, thus the research aims to investigate the mechanism of the relationship between celebrity endorsements with its three dimensions; attractiveness, trustworthiness and expertise with its relationship to customer experience multi dimensions. The research results revealed that there is a crucial relationship between celebrity endorsement based on its three dimensions (attractiveness, trustworthiness and expertise) and customer experience. However, not all the celebrity endorsement’s dimensions are equally influencing the customer experience.